Chemical Immunology and Allergy 2007
DOI: 10.1159/000099272
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Diseases – Anterior Uveitis

Abstract: Uveitis is a general term for inflammatory disorders of the uveal tract and encompasses a wide range of underlying etiologies. It may be idiopathic, associated with systemic diseases or result from a variety of infectious agents. Uveitis is responsible for over 2.8% of blindness in the United States. Each year, 17.6% of active uveitis patients experience a transient or permanent loss of vision. Anterior uveitis (AU), which refers to inflammation within the anterior segment of the eye, is the most common form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…A recent report from the Northern California Epidemiology Study suggested a higher disease rate for the older population in the US. 1,2 Anterior uveitis (AU) is a term that refers to inflammation within the anterior segment of the eye; retinal involvement is not a component of AU. [1][2][3] Idiopathic AU is the most common form of intraocular inflammation in humans and the recurrent nature of the disease can lead to permanent visual loss.…”
Section: Experimental Autoimmune Anterior Uveitis (Eaau)mentioning
confidence: 99%
See 3 more Smart Citations
“…A recent report from the Northern California Epidemiology Study suggested a higher disease rate for the older population in the US. 1,2 Anterior uveitis (AU) is a term that refers to inflammation within the anterior segment of the eye; retinal involvement is not a component of AU. [1][2][3] Idiopathic AU is the most common form of intraocular inflammation in humans and the recurrent nature of the disease can lead to permanent visual loss.…”
Section: Experimental Autoimmune Anterior Uveitis (Eaau)mentioning
confidence: 99%
“…1,2 Anterior uveitis (AU) is a term that refers to inflammation within the anterior segment of the eye; retinal involvement is not a component of AU. [1][2][3] Idiopathic AU is the most common form of intraocular inflammation in humans and the recurrent nature of the disease can lead to permanent visual loss. [1][2][3] Idiopathic AU is a disease that is associated with significant morbidity and can only be treated symptomatically, but not cured.…”
Section: Experimental Autoimmune Anterior Uveitis (Eaau)mentioning
confidence: 99%
See 2 more Smart Citations
“…Anterior uveitis (AU) 2 refers to the inflammation of the anterior segment of the eye, which includes the iris and the ciliary body (CB). Idiopathic AU is the most common form of intraocular inflammation in humans (1)(2)(3). Experimental autoimmune anterior uveitis (EAAU) is an organ-specific autoimmune disease of the eye that serves as an animal model of noninfectious autoimmune idiopathic AU (4 -15).…”
mentioning
confidence: 99%